Clinicopathological analysis of cervical polyps - Gopalan, Ushadevi; Rajendiran, Sathiyakala; Karnaboopathy, Ranganathan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical polyps are the commonest cervical lesions and occur in about 2-5% of women. It is common practice to remove these polyps whenever they are identified and the main reason for this is the concern over the potential for malignant transformation. This study was done to analyse the spectrum of histopathological diagnosis in cases of cervical polyps and to identify focus of malignancy if present. This would help us to improve further management of cases of symptomatic and asymptomatic cervical polyps Methods: This study was conducted in the department of Obstetrics and Gynecology in a tertiary care teaching hospital over a period of two years. Women with a polypoidal growth from the cervix visualized on per speculum examination were included in the study. Polypectomy was done and the specimen sent for histopathological examination and the data analysed. Results: Total of 107 women was included in the study. Most of the women (47.7%) were in the age group 40-49 years. Endocervical mucous polyp was found to be the most common lesion (50.5%) followed by benign endometrial polyp (21.5%), and leiomyomatous polyp in 13.1%. There were no foci of malignancy identified in any of these polyps. Conclusions: As the incidence of malignancy in endocervical polyp is very low, it is suggested that in cases of asymptomatic polyps, there is a role for expectant management with no intervention and these patients can be followed up leading to significant savings in health resources